The effect of aromatherapy with rosa damascena essence on postoperative pain in inguinal hernia repair: A randomized clinical trial - Abolfazl Amini; Nasrin Bahraminejad; Samineh Jafari; Koorosh Kamali (Kashan University of Medical Sciences, 2020)
Background: Despite therapeutic interventions, patients are still dissatisfied with the treatment of postoperative pain. Objectives: The aim of this study was to examine the effect of Rosa damascena essential oil on postoperative pain in patients undergoing inguinal hernia repair surgery. Methods: In a double-blind, randomized trial, 60 patients undergoing inguinal hernia repair surgery were selected consecutively and equally assigned to two groups of experimental and placebo. In both groups, the pain intensity was measured by a visual analog scale in 4, 8, and 12 h after the surgery. Patients in the experimental group received aromatherapy with R. damascena essential oil and those in the placebo group treated with almond oil. In both groups, pain intensity was measured before and 20 min after aromatherapy. Data analysis was performed using the repeated-measures analysis, analysis of covariance, independent-samples t- test, Chi-square, and Fisher's exact tests. Results: The mean pain intensity in the experimental and the placebo groups was 7.10 ± 1.24 versus 7.20 ± 1.10, 4.56 ± 1.04 versus 4.90 ± 0.84, and 1.30 ± 0.79 versus 2.46 ± 0.68 after the 4th, 8th, and 12th postsurgical hours, respectively. The repeated-measures analysis showed that the intervention was effective on pain reduction, especially in the 8th and 12th postoperative hours when the pain was at moderate-to-mild levels (P < 0.001). Conclusion: Aromatherapy with R. damascena essential oil was effective in relieving mild to moderated postoperative pain. Yet, further studies are needed to confirm this finding.